Pengaruh Net Profit Margin, Earning Per Share, Return On Equity, Price Earning Ratio, dan Debt To Equity Ratio terhadap Harga Saham - Risdanya, Mentari; Zaroni, Zaroni (Ultimaccounting Jurnal Ilmu Akuntansi, 2015)
This study aims to determine whether Net Profit Margin (NPM), Earning Per Share (EPS), Return On Equity (ROE), Price Earning Ratio (PER), and Debt to Equity Ratio (DER) have significant influence towards share price. The object of this research are companies in the field of property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2011-2013. Data collection methods used are secondary data from the annual financial statements. Sampling was done by using purposive sampling method, and the total sample used were 26 companies, the number of observed data 78 data. The data analysis technique used in this study is multiple regression analysis. The results of this study are (1) Net Profit Margin (NPM), Return On Equity (ROE), and Price Earning Ratio (PER) have no significant effect towards share price (2) Earning Per Share (EPS) and Debt to Equity Ratio (DER) have a significant effect towards share price. Keywords: Net Profit Margin, Earning Per Share, Return On Equity, Price Earning Ratio, Debt to Equity Ratio, Share Price.